A Purchaser's Guide to Clinical Preventive Services: A Tool to Improve Health Care Coverage for Prevention - Kathryn Phillips Campbell, MPH; Dyann M. Matson Koffman, DrPH, MPH, CHES; Andrew Lanza, MPH, MSW (Centers for Disease Control and Prevention, 2008)
IntroductionIn 2005, representatives from the Centers for Disease Control and Prevention partnered with the National Business Group on Health and the Agency for Healthcare Research and Quality to form a work group for developing A Purchaser's Guide to Clinical Preventive Services: Moving Science into Coverage. This guide, designed as a tool for employers, describes recommended clinical preventive services for 46 conditions. The guide includes the scientific evidence and benefits language that employers need to include comprehensive clinical preventive services in their medical benefit plans.MethodsThe work group determined that the guide would address conditions that 1) affected a large percentage of the working population, 2) were costly to control, and 3) had well-defined and accepted recommendations for preventive services. Subject matter experts from the Centers for Disease Control and Prevention, the National Business Group on Health, and the Agency for Healthcare Research and Quality developed or reviewed statements of scientific evidence for 46 diseases and conditions.ResultsThe Purchaser's Guide, written for an employer audience, includes descriptions for recommended clinical preventive services and their cost savings, syntheses of supporting evidence, strategies for prioritization, and recommendations to improve the delivery and use of preventive services. Twelve hundred copies were sent to more than 275 members of the National Business Group on Health and other purchasers of health care; training sessions on the Guide were held for 228 business leaders, health benefit consultants, and health plan administrators; and an online version was created through the Web sites of the National Business Group on Health and the Centers for Disease Control and Prevention. The online version has received more than 260,000 hits since its release.ConclusionIn 2007, the National Business Group on Health reported that some Fortune 500 companies will be using the Purchaser's Guide when negotiating their health benefit contracts and developing their health care strategies. Further research is under way to determine whether the Guide influences employers to purchase recommended clinical preventive services.